Changes in how English FAL learners appreciate poetry when indigenous poetry is brought into the classroom: a practitioner case study of grade 11 learners in Gauteng - Mavhiza, Grace (My University, 2019)
A vigorous poetry tradition has existed throughout South African history. It represents in many ways a truly original contribution to the literature in the English first additional language (FAL) classroom. The benefits of poetry in enhancing intellectual, emotional social and linguistic development in learners are well documented. Surprisingly, there is a negative attitude towards poetry by learners and teachers as they prefer other literary genres particularly in a secondary school where this research was carried out. I have realised that the oral traditional poetry which is an African form of poetry practice is largely absent in the classroom today. Through a practitioner case study, this research sought to elicit the Grade 11 learners’ changes in appreciation of classroom poetry when indigenous poetry is brought into the English FAL classroom. This study presents previous research regarding perceptions accorded to classroom poetry. This is a qualitative study in which data gathered through questionnaires, face-to-face interviews, poetry texts analysis and reflective writing was presented to answer the primary question; what could be the changes in the appreciation of classroom poetry if indigenous poetry is brought into the classroom? The findings show that learners of English FAL do not appreciate classroom poetry due to the reasons that; classroom poetry is distant from the learners‘ life experiences making them struggle to interpret the poetry prescribed for them. Learners also said that classroom poetry is boring and this is due to the teaching methods employed in the classroom which are book centred and assessment driven. However, this study concluded through the intervention that encouraging learners to respond to poetry by presenting poems in a range of modes is more likely to boost their interest than focusing on the “traditional” line by line analysis of poems. The other important finding is that if indigenous poetry is brought into the classroom, learners’ attitudes towards classroom poetry will positively change
A research report submitted in partial fulfillment of the requirements for the degree of Master in Education: Languages, literacies and literatures May 2019